1984
DOI: 10.1179/bjo.11.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on Spacing in the Normal Deciduous Dentition of 100 Indian Children from Gujarat

Abstract: Plaster casts of 50 boys and 50 girls aged 3–6 years, from Gujarat, India, were studied to observe the pattern of spacing in the normal deciduous dental arches. Spaced type of dental arches were more common than closed type or ‘no spaces’ type. Spacing/no spacing appeared to behave independently between upper and lower arches and between the sexes. The amount of spacing was greater in males than in females. Bilateral anthropoid spaces did not exist as a single phenomenon. They occurred when some other spaces w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 3 publications
8
14
0
Order By: Relevance
“…In the current study primate spaces were observed in the majority of the kids in the maxillary arch 89.8% & less percentage 81% was registered in the mandibular arch. These results correspond with the findings of previous investigations including Egyptian ,Iranian, Nigerian, Jordanian & Indian kids where primate spaces was registered more frequent in the upper arch than in the lower arch (7)(8)(9)26) . But, the prevalence is a slight higher in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study primate spaces were observed in the majority of the kids in the maxillary arch 89.8% & less percentage 81% was registered in the mandibular arch. These results correspond with the findings of previous investigations including Egyptian ,Iranian, Nigerian, Jordanian & Indian kids where primate spaces was registered more frequent in the upper arch than in the lower arch (7)(8)(9)26) . But, the prevalence is a slight higher in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Lack of spaces in the deciduous teeth is an representation of disproportion concerning tooth and jaw size. Prevalence of spacing in the primary dentition varies between different ethnic and populations groups (7)(8)(9) . The distal step relationship of the primary molar teeth commonly result in Angel class II molar relation whereas smaller number of mesial step cause class III molar relation.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of malocclusion in India has been observed to be ranging from 20% to 43% [27] Class I malocclusion ranges from 66.7% in the desert state of Rajasthan 7(North India) to 49.2% in Bangalore (south India)34 to 91.6% in 5-9 year age group and 27.7% in 10-13 years age group in New Delhi (Central India) [34]. These results shows lesser prevalence of Class I malocclusion as compared 62.9% in Latino Adolescents as was observed by Silva RG et al [35] and 80.7% in Benin City, Nigeria as observed by Emmanuel OA in his study sample [36].…”
Section: Discussionmentioning
confidence: 99%
“…Spacing on the left side was more common than right side. Spacing between the mandibular incisors was the greatest of all [27].…”
Section: Gujaratmentioning
confidence: 95%
See 1 more Smart Citation